IMPROVING THE INDONESIAN’S MINE COUNTERMEASURE SMART MINE CAPABILITY BY ANALYTIC HIERARCHY PROCESS AND MEASUREMENT OF EFFECTIVENESS METHODS - Hariwibowo, Rendra; Arief, Ruslan (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2022)
Mine warfare is still developing in line with technological developments. Technological developments in the field of mines have produced smart mines that can select targets as desired precisely and accurately. Currently, minehunting vessels are owned by the Indonesian Navy. In this study, an analysis of the capability of minehunting vessels class will be carried out including the capability of the sensor weapon command system, the professionalism of the crew, and Explosive Ordnance Disposal (EOD) divers as well as ship degaussing systems. This study aims to analyze the ability of the class mine-hunting ships of the Indonesian Navy to deal with modern mine warfare, especially to deal with mines that can choose their targets or often called Smart Mines. This study uses quantitative research methods, namely data analysis with Measures Of Effectiveness (MOE) and Analytical Hierarchy Process (AHP) methods. This study found that the increase in Sewaco's ability to deal with modern mine warfare will also have to be followed by improvements or changes in tactics and strategies that are adapted to the increase in the ship's capabilities. This increase in the professionalism of soldiers is carried out at all levels of rank, starting from officers through Mine Warfare Officer (MWO) education either organized by the Navy or abroad, then at the non-commissioned and enlisted levels to improve their skills carried out through regular and scheduled training. Mine ships with a good degaussing system function will be very supportive in carrying out mine operations, stating that modern sea mines are equipped with sensors or magnetic sonar that are placed on the sea surface or below sea level. For this reason, the function of the degaussing system must be able to operate properly in the face of these modern mines.